Opinions and perceptions on acne:A community-based questionnaire study in Thai students - Puan Suthipinittharm (2018)
Objective: To evaluate the opinions and perceptions on acne and the effect of acne on the quality of life in Thai teenagers. Material and Method: Five hundred ninety seven students of five high schools in Bangkok were administered a self-reported questionnaire about acne. Of these, 537 students were further examined by dermatologists to grade acne severity. Results: The study population consisted of 392 (65.7%) female and 205 (34.3%) male. More than half believed that inadequate sleep, stress, sweat/exercise/hot weather, cosmetics, pre-menstrual period, oily food, and sun exposure aggravated their acne. Regarding Dermatology life quality index (DLQI), the question concerning embarrassment had the highest mean DLQI score, which reflect the most impact by acne. Conclusion: Some of the Thai adolescents still had misconceptions about the disease. Even mild acne can have an extremely large effect on their quality of life.